1999
DOI: 10.1177/000331979905000806
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Baroreflex Sensitivity Assessed from Phase IV of Valsalva Maneuver in Mild Congestive Heart Failure

Abstract: Decreased sensitivity of cardiopulmonary and arterial baroreceptors has been hypothesized to sustain sympathetic activation in patients with heart failure. In the present investigation the relationship between the impairment of baroreflex sensitivity and clinical severity of congestive heart failure was investigated. The authors studied 58 patients with heart failure (14 in NYHA class I, 22 in NYHA class II, and 22 in NYHA class III), 38 women and 20 men, age range 28-65 years. Thirty-two patients suffered fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…Furthermore, the number of frequent or seldom word types was less in DCM than in CON. This also points at a loss of HRV mediated by an impaired blood pressure regulation in DCM that has been described by other authors [21].…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, the number of frequent or seldom word types was less in DCM than in CON. This also points at a loss of HRV mediated by an impaired blood pressure regulation in DCM that has been described by other authors [21].…”
Section: Discussionsupporting
confidence: 81%
“…In patients with PD, Lewy bodies are found mainly in the brain stem; autonomic symptoms frequently coexist with core motor impairments, such as tremor, extremity rigidity, bradykinesia, and postural instability. For instance, OH affects from 20% to 50% of patients with PD [5][6][7][8][9][10]. However, autonomic function in DLB has received little attention and has not been studied systematically [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…11 Previous studies have demonstrated the high reproducibility and close relation between the Valsalva method and the phenylephrine method. 10,18 Rostangno et al reported that the BRS obtained by the Valsalva method could predict worsening outcome in patients with ventricular dysfunction 19 and the BRS value obtained in the present study is similar to theirs, which suggests that BRS is reduced in patients who have experienced an AMI.…”
Section: Measurement Of Brs Using the Valsalva Maneuversupporting
confidence: 86%